Construction of a large-tonnage fleet in Russia: problems, prospects, innovations - D. G. Bigvava; A. Y. Smirnov (Интеллект. Инновации. Инвестиции, 2023)
The construction of a large-tonnage fleet is an important factor in the development of maritime trade and the economy as a whole. In recent years, Russian shipbuilders have faced a number of problems that negatively affect the pace of socio-economic development of the industry, do not allow to fully use its potential in the production of civilian products. The purpose of the article is to identify the main problems in the process of building a large–tonnage fleet in the Russian Federation, to indicate the prospects for the development of the industry. The main content of the conducted research is the analysis of statistical data on the number of ships produced, up-to-date information reflecting the current state of production capacities of shipbuilding and ship repair enterprises in Russia is presented, its own definition of the concept of «large-tonnage vessel» is specified and proposed for further use. According to the results of the study, it was concluded that the effective development of large-tonnage shipbuilding in our country is hindered by such problems as: high design and construction costs, a shortage of qualified personnel, lack of intersectoral cooperation, an acute shortage of ship components of domestic production, which negatively affects the pace of development of the industry due to the ban on the supply of products from unfriendly countries, a high degree of depreciation of fixed assets of shipbuilding industry enterprises. The lack of a systematic approach to solving these problems, the insufficient effectiveness of the existing mechanisms of interdepartmental and intersectoral interaction, negatively affect the results of the activities of shipbuilding enterprises and the development of their production potential, both in the current period of time and in the long term. In order to increase the volume of construction of large-tonnage vessels at the shipyards of the Russian Federation, it is necessary to allocate financial resources from the federal budget (or at the expense of the National Welfare Fund of Russia) for the modernization and production capacities of enterprises with the necessary competencies for the construction of large-sized vessels, implement a set of measures aimed at full utilization of production capacities through cooperation, provide preferential financing to manufacturers of ship equipment.